Highly improved PP/CNTs sheet prepared by tailoring crystallization morphology through solid‐phase die drawing and multilayer hot compression. Issue 4 (13th July 2020) - Lin, Xiang; Spencer, Paul; Gong, Min; Coates, Phil
Abstract: Simply melt blended polypropylene/carbon nanotubes composites (PP/CNTs) usually present mechanical deterioration. In this work, multilayered sheet of PP/CNTs with improved tensile property was obtained by solid‐phase orientation and hot compression. The initially blended PP/CNTs were highly orientated by employing a constrained slit die and hot compressed under a certain temperature and pressure by stacking eight layers together. The effects of compression temperature and pressure on the tensile property and AC conductivity of the multilayered sheets were examined to explore the evolution of hierarchical crystallization morphology and CNT networks. The multilayered sheet which was hot compressed at 184°C and 5 MPa demonstrated an optimum tensile strength of ∼132.5 MPa and an elongation at break ∼52.7%, respectively, raised by almost 3‐fold compared with those initially blended PP/CNTs. By increasing compression temperature and decreasing pressure, the AC conductivity showed an increase of 2 to 4 orders of magnitude. Abstract : A way to produce highly orientated crystallization morphology for PP/CNTs composite has been explored by solid‐phase orientation and hot compression. The highest tensile strength up to ∼132.5 MPa and an improved breaking strain up to ∼52.7% for as‐prepared sheet have been achieved, which is increased by ∼3 times than those of initially blended composite.